Relationship between Nucleus Swelling and Development Competence of Bovine Cloned Embryos Reconstructed by Enucleated Oocytes with Serum-starved or Serum-fed Fetal Somatic Cells - Fahrudin, Mokhamad; Karja, Ni Wayan Kurniani; Suzuki, Tatsuyuki (Indonesian Journal of Biotechnology, 2005)
This study was conducted to examine the occurrence of nuclear remodeling (nucleus swelling) and its effectson the subsequent in vitro development of bovine embryos reconstructed by serum-starved and serum-fed somaticcells. Results from this study demonstrated that all of the reconstructed embryos that received serum-starved andserum-fed somatic cells exhibited condensed-nuclei. More than 90% of the transferred nuclei exhibited nuclearenvelope breakdown and premature chromatin condensation which clearly distinct from an intact nucleus. Therewas no significant difference on the degree of nucleus swelling in SS-NT embryos or SF-NT embryos, indicatingthat either serum-starved or confluent somatic cell lines could be reprogrammed by the recipient cytoplasmenvironments in similar pattern. Although the fusion rate was not significantly different among the groups, theproportion of SS-NT embryos which developed to the 2- to 4-cell stage (89.7%) and to the 8- to 16-cell stage (74.7%)was significantly higher than that of SF-NT embryos. Whereas, the proportion of reconstructed embryos thatdeveloped to the morula and blastocyst stages were not significantly different among the groups. Results of thesestudies demonstrate that reconstructed embryos, which received either serum-starved or serum-fed confluentsomatic cells, showed similar developmental competence to the blastocyst stage.Keywords: nuclear transplantation technique-somatic cells-nucleus swelling